Prevalence and correlates of physical disability and functional limitation among community dwelling older people in rural Malaysia, a middle income country - Hairi, Noran Naqiah; Bulgiba, Awang; Cumming, Robert G.; Naganathan, Vasi; Mudla, Izzuna (BioMed Central, 2010)
Background: The prevalence and correlates of physical disability and functional limitation among older people have been studied in many developed countries but not in a middle income country such as Malaysia. The present study investigated the epidemiology of physical disability and functional limitation among older people in Malaysia and compares findings to other countries. Methods: A population-based cross sectional study was conducted in Alor Gajah, Malacca. Seven hundred and sixty five older people aged 60 years and above underwent tests of functional limitation (Tinetti Performance Oriented Mobility Assessment Tool). Data were also collected for self reported activities of daily living (ADL) using the Barthel Index (ten items). To compare prevalence with other studies, ADL disability was also defined using six basic ADL's (eating, bathing, dressing, transferring, toileting and walking) and five basic ADL's (eating, bathing, dressing, transferring and toileting). Results: Ten, six and five basic ADL disability was reported by 24.7 (95 CI 21.6-27.9), 14.4 (95 CI 11.9-17.2) and 10.6 (95 CI 8.5-13.1), respectively. Functional limitation was found in 19.5 (95 CI 16.8-22.5) of participants. Variables independently associated with 10 item ADL disability physical disability, were advanced age (>= 75 years: prevalence ratio (PR) 7.9; 95 CI 4.8-12.9), presence of diabetes (PR 1.8; 95 CI 1.4-2.3), stroke (PR 1.5; 95 CI 1.1-2.2), depressive symptomology (PR 1.3; 95 CI 1.1-1.8) and visual impairment (blind: PR 2.0; 95 CI 1.1-3.6). Advancing age (>= 75 years: PR 3.0; 95 CI 1.7-5.2) being female (PR 2.7; 95 CI 1.2-6.1), presence of arthritis (PR 1.6; 95 CI 1.2-2.1) and depressive symptomology (PR 2.0; 95 CI 1.5-2.7) were significantly associated with functional limitation. Conclusions: The prevalence of physical disability and functional limitation among older Malaysians appears to be much higher than in developed countries but is comparable to developing countries. Associations with socio-demographic and other health related variables were consistent with other studies.